Least Mastered Competencies of Grade 11 Students in Oral Communica-tion: Basis for Development and Evaluation of Contextualized E-Learning - Aceron, Ma. Morena Centeno (Future Science / FSH-PH Publications, 2023)
This study aimed to develop based on the students' least mastered competencies for the academic year 2021–2022, this study sought to develop and evaluate contextualized e-learning enhancement activities in Oral Communication in Context for Grade 11 Senior High School of San Isidro National High School District I–C in the City Division of Antipolo. Descriptive research was the method of inquiry used in this study. The study involves the evaluation of the created contextualized E-learning enhancement activities in Oral Communication in Context for Grade 11 among students, teachers, and experts. To assess the suitability of the created learning materials in terms of appropriateness, authenticity, and clarity, the researcher created a tool in the form of a questionnaire that was evaluated by a panel of experts in the field of English.